Stimulation of physical fitness through traditional games in elementary school students: A systematic review in Indonesia - Suryadi, Didi; Ivanov, Danail; Zulnadila, Zulnadila (Khatulistwa Education Center, 2025)
Background Physical fitness plays a crucial role in supporting elementary school students’ ability to engage in learning activities without experiencing excessive fatigue. Adequate fitness levels enable students to maintain concentration and participate actively in school tasks. In Indonesia, information regarding the physical fitness of elementary school children remains limited, despite its importance for promoting overall health and learning readiness. Objectives This systematic review aims to examine the existing scientific literature on the role of traditional games as a learning strategy to improve physical fitness among elementary school students in Indonesia. Methods A systematic search was conducted across four major databases—ScienceDirect, Scopus, Google Scholar, and PubMed. The search strategy employed a combination of keywords, including (“traditional games” OR “play model”) AND “physical fitness” AND “students” AND “elementary school.” The review process followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, including screening, eligibility assessment, and data extraction from relevant studies. Results The findings indicate that traditional games positively contribute to improving students’ physical fitness. These games are typically designed using a play-based approach and incorporate activities aligned with children’s fundamental motor skills and developmental stages. Improvements occur because traditional games encourage active participation, increase movement engagement, and support effective fitness development within physical education settings. Conclusion Traditional games represent an effective and culturally relevant strategy for enhancing physical fitness among elementary school students in Indonesia. Their integration into physical education classes can promote active learning and contribute to better health outcomes. This review provides comprehensive evidence on the pedagogical value of traditional games in improving children’s physical fitness, highlights their relevance for culturally grounded physical education practices, and offers insights for researchers, educators, and policymakers seeking to optimize school-based fitness interventions.